(untitled) (Stato, Chiese e pluralismo confessionale, 2020)
SOMMARIO: 1. L’estensione degli artt. 604-bis e 604-ter del codice penale - 2. La disciplina attualmente in vigore - 3. La mancanza di determinatezza di alcune fattispecie previste nel Testo unificato - 4. Il fine di sanzionare la violenza e altri fatti criminosi - 5. Il fine di prevenire la violenza, le manifestazioni di un pensiero discriminatorio e la discriminazione come tale - 6. Sull’equilibrio tra libertà ed eguaglianza. The Ends Do Not Justify the Means. Considerations on The Bill on “Violence or Discrimination on Grounds of Gender or Sexual Orientation” ABSTRACT: This article analyzes the legislative proposal on “violence or discrimination on grounds of gender or sexual orientation” currently under examination by the Italian Parliament. It exposes how, according to the bill, three types of behaviour would be punished under penal law: violent acts or incitements to violence, discriminatory acts, expression of discriminatory thoughts. The author shows why the new law would infringe the Italian Constitution in so far as it forbids the expression of ideas or punishes acts that have no link with violence. This would contrast with several fundamental freedoms such as the freedoms of expression, of assembly and of religion.